Plasmonic substrates comprising gold nanostars efficiently regenerate cofactor molecules. Issue 18 (7th April 2016) - Sánchez-Iglesias, Ana; Barroso, Javier; Solís, Diego M.; Taboada, José M.; Obelleiro, Fernando; Pavlov, Valeri; Chuvilin, Andrey; Grzelczak, Marek
Abstract : Gold nanostars as a photocatalyst perform better than rods and cubes. Abstract : The light harvesting capacity of plasmonic nanoparticles is a fundamental feature for catalysing chemical reactions close to their surface. The efficiency of the photochemical processes depends not only on the geometrical aspects on a single particle level but also on the complexity of the multiparticle architectures. Although, the effect of the particle geometry is progressively understood in the relevant photochemical processes (water splitting and hydrogen evolution), there are experimental and theoretical needs for understanding the role of the shape in the multiparticle systems in the photocatalytic processes. Here we have shown that macroscopic plasmonic substrates comprising gold nanostars exhibit better efficiencies than nanorods or cubes in the photoregeneration of cofactor molecules. We performed photochemical and photoelectrochemical measurements, supported by theoretical simulations, showing that the unique geometry of nanostars – radially distributed spikes – contributes to stronger light absorption by the plasmonic film containing that type of nanoparticles.